2003
DOI: 10.1002/jbm.a.10021
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing mechanical properties of tissue‐engineered constructs via lysyl oxidase crosslinking activity

Abstract: A number of strategies have been investigated to enhance the mechanical stability of engineered tissues. In this study, we utilized lysyl oxidase (LO) to enzymatically crosslink extracellular matrix (ECM) proteins, particularly collagen and elastin, to enhance the mechanical integrity of the ECM and thereby impart mechanical strength to the engineered tissue. Vascular smooth muscle cells (VSMCs) were liposomally transfected with the LO gene. Both Northern and Western analyses confirmed increased LO expression.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
80
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(84 citation statements)
references
References 32 publications
4
80
0
Order By: Relevance
“…This is not surprising given in vitro data that LOX treatment of isolated collagen gels resulted in a significant increase in GЈ (12,22). In vivo studies of rat heart and aorta also showed that increased stiffness was secondary to cross-linking by members of the LOX family rather than to increased collagen deposition (4,30,37).…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…This is not surprising given in vitro data that LOX treatment of isolated collagen gels resulted in a significant increase in GЈ (12,22). In vivo studies of rat heart and aorta also showed that increased stiffness was secondary to cross-linking by members of the LOX family rather than to increased collagen deposition (4,30,37).…”
Section: Discussionmentioning
confidence: 83%
“…We hypothesized that early changes in GЈ resulted from increased collagen cross-linking, which has been shown in in vitro as well as in vivo studies to increase the GЈ of collagen in the absence of increased deposition. Lysyl oxidase (LOX)-mediated cross-linking activity in particular increases collagen stiffness and is known to be upregulated early after liver injury (4,12,22,30,37). We therefore treated a second cohort of rats with the LOX inhibitor BAPN over a period of 2 wk.…”
Section: Study Design and Histologymentioning
confidence: 99%
“…There are five isoforms: LOX and the LOX-like enzymes LOXL1, LOXL2, LOXL3, and LOXL4, all encoded by separate genes and with overlapping, but distinct, functions and substrate specificity. Multiple studies have shown that LOX-mediated cross-linking significantly increases ECM stiffness (8,15,20,29).The LOXs play an important role in liver fibrosis. LOX expression in the liver, as determined by immunohistochemistry, is upregulated as early as 24 h after bile duct ligation (BDL) and continues to increase through at least 72 h, preceding increases in ␣-SMA (7).…”
mentioning
confidence: 99%
“…There are five isoforms: LOX and the LOX-like enzymes LOXL1, LOXL2, LOXL3, and LOXL4, all encoded by separate genes and with overlapping, but distinct, functions and substrate specificity. Multiple studies have shown that LOX-mediated cross-linking significantly increases ECM stiffness (8,15,20,29).…”
mentioning
confidence: 99%
“…Because collagen I is the most common protein found in vertebrate animals and is structurally highly conserved, it is generally well tolerated for in vivo studies, and multiple cell types readily adhere to this substrate. In addition, the elastic moduli of a collagen I gel can be readily manipulated by varying collagen orientation, fibril crosslinking, concentration, or even biochemical modification or mutation (Christner et al, 2006;Girton et al, 1999;Martin et al, 1996;Roeder et al, 2002), thereby increasing its biological versatility (Elbjeirami et al, 2003;Grinnell, 2003). The magnitude and directional orientation of externally imposed tension can also be easily manipulated with collagen preparations.…”
Section: D Organotypic Model Systemsmentioning
confidence: 99%